Ethnocultural images in postcolonial publications in the Russian-language prose of the Korean diaspora - Safronova, Lyudmila; Bekmuratova, Aygerim (Przegląd Wschodnioeuropejski, 2020)
The literature of the Korean diaspora of the former Soviet Union combines the national characteristics of the Korean culture of the metropolis, the Korean national mentality, and at the same time reflects the historical realities and difficult, sometimes tragic fates of all peoples of the USSR and post-Soviet period. In this respect, the evolution of the literature of the Korean diaspora, leading from the prose in Korean to the first settlers from Korea to Sakhalin, was shown, which later were deported by Stalin’s decree to Kazakhstan and Uzbekistan. The literature of the Korean diaspora in Kazakhstan goes through all stages of the development of Soviet literature – from anti-Stalin prose, romanticized thaw literature and “quiet” stagnation prose, to postmodern and feminist literature. Moreover, Confucianism and Christian motives, Buddhism and Taoism, shamanism and Russian traditional literary images, motives, and themes are organically intertwined in the work of Russian and Kazakhstani Koreans. However, crosscutting issue through all the work of Korean writers who find themselves outside their homeland, it is an appeal to national identity, attempts to acquiring, preserving or tragedy and the pain of loss.